(untitled) (European Journal of Pure and Applied Mathematics, 2023)
Ideals in BCK/BCI algebra based on Y_J^ε-fuzzy sets are studied. The fundamental properties of the level set of Y_J^ε-fuzzy sets are investigate first. The concept of (closed) Y_J^ε-fuzzy ideals in BCK/BCI-algebras is introduces, and several properties are investigated. The relationship between Y_J^ε-fuzzy ideal and Y_J^ε-fuzzy subalgebra are discussed, and also the relationship between Y_J^ε-fuzzy ideal and fuzzy ideal is identified. The characterization of (closed) Y_J^ε-fuzzy ideal using the Y-level set is established. The necessary and sufficient conditions for Y_J^ε-fuzzy ideal to be closed is explored, and conditions for Y_J^ε-fuzzy subalgebra to be Y_J^ε-fuzzy ideal are provided.